Photon antibunching in single molecule fluorescence spectroscopy - Grußmayer, Kristin Stefanie; Herten, Dirk-Peter (Advanced photon counting, 2015)
Single molecule fluorescence spectroscopy (SMFS) opened an important pathway for studying properties of individual quantum systems under ambient conditions. One such fundamental characteristic is based on the fact that single emitters can only emit single photons. This leads to the phenomenon of antibunching, that is, the probability for detecting multiple photons approaches zero for decreasing detection time windows shorter than the excited state lifetime. In the last decade photon antibunching has regained interest by many researchers in the field of SMFS for two main reasons. First, the observation of antibunching by measuring photon correlations could easily be transferred to become the only direct proof that a single fluorescing molecule is observed. This is crucial for quantum information processing, quantum cryptography, and metrology. Second, its characteristic photon statistics could be exploited for estimating the number of independently emitting molecules with a confocal fluorescence microscope. Recent applications aim at understanding mechanisms of energy transfer in multichromophoric molecules and photo-systems and at quantifying copy numbers in protein complexes. This chapter highlights different methods to measure photon antibunching in SMFS experiments. Aside from technical aspects we will consider the fundamental theories that are used for data analysis. Each methodological approach is then followed by a section illustrating the respective applications of photon antibunching.
Gesehen am 19.01.2021
Published online: 18 December 2014